Achieving sub-nanometre particle mapping with energy-filtered TEM. - Lozano-Perez, S; de Castro Bernal, V; Nicholls, R (2009)
A combination of state-of-the-art instrumentation and optimized data processing has enabled for the first time the chemical mapping of sub-nanometre particles using energy-filtered transmission electron microscopy (EFTEM). Multivariate statistical analysis (MSA) generated reconstructed datasets where the signal from particles smaller than 1 nm in diameter was successfully isolated from the original noisy background. The technique has been applied to the characterization of oxide dispersion strengthened (ODS) reduced activation FeCr alloys, due to their relevance as structural materials for future fusion reactors. Results revealed that most nanometer-sized particles had a core-shell structure, with an Yttrium-Chromium-Oxygen-rich core and a nano-scaled Chromium-Oxygen-rich shell. This segregation to the nanoparticles caused a decrease of the Chromium dissolved in the matrix, compromising the corrosion resistance of the alloy.